The management of the covid-19 health crisis in Spain: Effects on the organization and functioning of the decentralized state - Pérez Medina, José María (Razón y fe, 2022)
The covid-19 crisis has highlighted the lack of clarity in the role of the State Administration and the Ministry of Health, in a system of sharing functions in which the State lacks its own healthcare resources and, therefore, runs the risk of excessive distance from the real problems of the healthcare system. The current health regulations have proved to be insufficient and may require additional regulatory provisions to ensure their effectiveness in the event of non-compliance.